Sistem Informasi Persewaan Mobil Berbasis Web Menggunakan Metode UML - Budiarto, Iwan, Aris Rakhmadi, S.T., M.Eng (2016)
Car rental is a business service area. Customers often found difficulties to look for the existence of the rental car information. Sometimes after finding the place, cars were rented not to be expected or the car is being rented by someone else. The purpose of this research are to help customers find car rental services and to simplify the order. Customers can make a reservation in this information system. In addition, the information system also provides information about rented car. Web based car rental information system is one of the efforts in providing information on rental car with the intent of expanding information and to simplify the ordering process. Car rental information system design using UML method. Graphical diagrams consist of use case diagram and activity diagram. The programming language used PHP and MYSQL database to save data. The results are provided in the information system is information about car rental and car reservations to facilitate the customers to book a car.